Disiplin Waktu Dalam Tafsir Al-Thabari: Jalan Menuju Pribadi Mandiri dan Produktif - Rosidin Rosidin; Siti Nur Haliza (AL - IBRAH, 2025)
This study aims to explore the meaning of time discipline as reflected in Surah Al-Muzammil and Surah Al-‘Asr, based on the interpretation of Imam Al-Ṭtabari in Jāmi‘ al-Bayān fī Ta’wīl al-Qur’ān, and its relevance to the formation of an independent and productive Islamic character. A qualitative approach was employed using the library research method, focusing on the analysis of Qur’anic texts and classical tafsir. The findings indicate that Surah Al-Muzammil emphasizes spiritual discipline through the command of qiyām al-lail (night prayer), which trains time awareness, self-control, and worship consistency. Meanwhile, Surah Al-‘Asr highlights the importance of time management in social life by promoting righteous deeds, patience, and mutual encouragement in goodness as criteria for those not among the losers. The study identifies a thematic continuity between the two surahs: one shapes the individual through internal spiritual discipline, while the other guides constructive social behavior. Thus, this research affirms that time discipline in the Qur’an is a comprehensive value that encompasses both inner and social dimensions. These findings are expected to contribute theoretically to the development of Qur’an-based character education, particularly in shaping responsible, independent, and action-oriented Muslim individuals.